2022
DOI: 10.1097/md.0000000000029822
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis as a rare adverse event among cannabis users: A systematic review

Abstract: Background: Cannabis use has been steadily rising in the United States and can have multiple adverse effects, including cannabis-induced acute pancreatitis. This study aims to collate and highlight the significant demographics, clinical presentation, and outcomes in patients with cannabis-induced acute pancreatitis. Method: A systematic literature search of electronic databases for peer-reviewed articles was conducted. After an initial search, we found 792 articles through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several case reports suggest the association of cannabis-induced pancreatitis[ 107 - 109 ]. Multiple systematic reviews found cannabis use was related to acute and recurrent pancreatitis and cannabis cessation evoked no further episodes[ 110 - 112 ]. One study found no impact of cannabis on disease severity or mortality[ 113 ].…”
Section: Role In the Gi Tractmentioning
confidence: 99%
“…Several case reports suggest the association of cannabis-induced pancreatitis[ 107 - 109 ]. Multiple systematic reviews found cannabis use was related to acute and recurrent pancreatitis and cannabis cessation evoked no further episodes[ 110 - 112 ]. One study found no impact of cannabis on disease severity or mortality[ 113 ].…”
Section: Role In the Gi Tractmentioning
confidence: 99%